A double-blind randomized controlled trial of the effects of eicosapentaenoic acid supplementation on muscle inflammation and physical function in patients undergoing colorectal cancer resection. Issue 7 (July 2020) - Hossain, Tanvir; Phillips, Bethan E.; Doleman, Brett; Lund, Jonathan N.; Williams, John P.
Summary: Background: Resection of colorectal cancer (CRC) initiates inflammation, mediated at least partly by NFĸB (nuclear factor kappa-light-chain-enhancer of activated B-cells), leading to muscle catabolism and reduced physical performance. Eicosapentaenoic acid (EPA) has been shown to modulate NFĸB, but evidence for its benefit around the time of surgery is limited. Objective: To assess the effect of EPA supplementation on muscle inflammation and physical function around the time of major surgery. Design: In a double-blind randomized control trial, 61 patients (age: 68.3 ± 0.95 y; 42 male) scheduled for CRC resection, received 3 g per day of EPA (n = 32) or placebo (n = 29) for 5-days before and 21-days after operation. Lean muscle mass (LMM) (via dual energy X-ray absorptiometry (DXA)), anaerobic threshold (AT) (via cardiopulmonary exercise testing (CPET)) and hand-grip strength (HG) were assessed before and 4-weeks after surgery, with muscle biopsies ( m. vastus lateralis ) obtained for the assessment of NF-ĸB protein expression. Results: There were no differences in muscle NFĸB between EPA and placebo groups (mean difference (MD) −0.002; 95% confidence interval (CI) −0.19 to 0.19); p  = 0.98). There was no difference in LMM (MD 704.77 g; 95% CI -1045.6 g–2455.13 g; p  = 0.42) or AT (MD 1.11 mls/kg/min; 95% CI -0.52 mls/kg/min to 2.74 mls/kg/min; p  = 0.18) between the groups. Similarly, there was no difference between the groups in HG at follow up (MD 0.1; 95% CI -1.88 to 2.08; p  = 0.81). Results were similar when missing data was imputed. Conclusion: EPA supplementation confers no benefit in terms of inflammatory status, as judged by NFĸB, or preservation of LMM, aerobic capacity or physical function following major colorectal surgery. Clinical trials reference: NCT01320319 .